Improvement of double-layer phosphor structure WLEDS in color homogeneity and luminous flux - Dieu An Nguyen Thi; Phung Ton That; Hoang Nam Nguyen (Bulletin of Electrical Engineering and Informatics, 2021)
The concept of the analysis is to put a CaAl2O4:Mn2+ green phosphor layer on top of the YAG:Ce3+ yellow phosphor layer. After that, find the added CaAl2O4:Mn2+ concentration appropriate for the highest luminous flux (LF) and color homogeneity (CH). In this analysis, five equivalent WLEDs were applied but with distinct color temperatures, including 5600 K - 8500 K. The findings showed that CaAl2O4:Mn2+ brings great benefits to increase not only the luminous flux but also the color homogeneity. Especially, the higher the CaAl2O4:Mn2+ concentration, the more the luminous flux released by WLEDs, owing to the risen content of the light of green in WLEDs. Nevertheless, as the CaAl2O4:Mn2+ concentration raised significantly, a small reduction in the color rendering metric (CRI) and color quality scale (CQS) occurred. This is supported by simulation and calculation according to the theory of Monte Carlo. The paper results are the crucial contribution to the manufacture of WLEDs with better optical performance and color homogeneity of remote phosphor configurations.